Revitalization of Pekan Labuhan Traditional Market (Behavioral Architecture) - Devin Defriza Harisdani; M.A.F.S Hadintha (Talenta Publisher, 2017)
Business opportunities and challenges in the economic sector are underway in the country, including in Medan Labuhan. Many regions build their territory by making public spaces such as traditional markets. Nowadays, there is a change of consumer behavior toward the traditional market so; its positions are replaced by the modern markets. With the revitalization of Pekan Labuhan traditional market that carries the theme of behavioral architecture is expected to restore the function of the traditional market as a place of selling and purchasing transaction and increasing competitiveness to the modern market. With the achievement of this issue will increase consumer interest to shop in Pekan Labuhan traditional market which then gives a good impact on the economic stability of Medan Labuhan.